2013
DOI: 10.1371/journal.pone.0068108
|View full text |Cite
|
Sign up to set email alerts
|

Dual Mechanisms of Translation Initiation of the Full-Length HIV-1 mRNA Contribute to Gag Synthesis

Abstract: The precursor group-specific antigen (pr55Gag) is central to HIV-1 assembly. Its expression alone is sufficient to assemble into virus-like particles. It also selects the genomic RNA for encapsidation and is involved in several important virus-host interactions for viral assembly and restriction, making its synthesis essential for aspects of viral replication. Here, we show that the initiation of translation of the HIV-1 genomic RNA is mediated through both a cap-dependent and an internal ribosome entry site (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 69 publications
5
63
0
Order By: Relevance
“…Therefore, our data do not support the conclusion of others suggesting that translation initiation from the full-length HTLV-1 mRNA is exclusively cap dependent (22), nor do they indicate that translation initiation from the full-length HTLV-1 mRNA is exclusively IRES dependent. Several studies have shown that primate lentiviruses exhibit a redundancy in the mechanism of initiation of protein synthesis (reviewed in reference 8), suggesting that these mRNAs can initiate translation using both a cap-dependent and an IRES-dependent mechanism (18,19). Based on the evidence and on the apparent conservation of functions among the Retroviridae (8), we expect the HTLV-1 full-length mRNA to also use dual cap-and IRES-mediated mechanisms of translation initiation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, our data do not support the conclusion of others suggesting that translation initiation from the full-length HTLV-1 mRNA is exclusively cap dependent (22), nor do they indicate that translation initiation from the full-length HTLV-1 mRNA is exclusively IRES dependent. Several studies have shown that primate lentiviruses exhibit a redundancy in the mechanism of initiation of protein synthesis (reviewed in reference 8), suggesting that these mRNAs can initiate translation using both a cap-dependent and an IRES-dependent mechanism (18,19). Based on the evidence and on the apparent conservation of functions among the Retroviridae (8), we expect the HTLV-1 full-length mRNA to also use dual cap-and IRES-mediated mechanisms of translation initiation.…”
Section: Discussionmentioning
confidence: 93%
“…The full-length mRNA of some retroviruses can initiate protein synthesis through both a cap-dependent and a cap-independent mechanism (8,18,19). At present, an IRES element is defined solely by performing a functional assay and cannot be predicted by the presence of characteristic RNA sequences or structural motifs (7,38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 In sharp contrast to picornavirus mRNAs, retroviral mRNAs possess a 5 0 cap structure and can initiate translation either by a canonical cap-dependent mechanism or via an IRES. 32,33 RNA Structures Modulate Protein Synthesis of the Full-Length HIV-1 mRNA…”
Section: Translation Initiationmentioning
confidence: 99%
“…132,133 In the case of the HIV-1, the 5 0 UTR has been shown to drive cap-dependent translation initiation under normal physiological conditions 33,51 and to mediate IRES-dependent protein synthesis during stress conditions known to hinder cap-dependent translation initiation. 32,86,88,91,118 Interestingly, in the course of viral replication, HIV-1 has been shown to change cellular homeostasis altering several components of the host translational apparatus which results in the inhibition of cap-dependent translation. For instance, HIV-1 induces an endogenous cellular increase of reactive oxygen intermediates leading to an oxidative stress that has been demonstrated to facilitate NF-kappa B-dependent activation of HIV transcription and to stimulate the HIV-1 5 0 UTR IRES activity.…”
mentioning
confidence: 99%